2020
DOI: 10.1111/jrh.12500
|View full text |Cite
|
Sign up to set email alerts
|

Rural‐Urban Differences in Dental Service Utilization and Dental Service Procedures Received Among US Adults: Results From the 2016 Medical Expenditure Panel Survey

Abstract: Purpose To assess rural‐urban differences in dental service use and procedures and to explore the interaction effects of individual‐ and county‐level factors on having dental service use and procedures. Methods Data were from the 2016 Medical Expenditure Panel Survey (MEPS). We assessed rural‐urban differences in 3 outcome variables: number of dental visits (1, 2, or 3+ visits), preventive care procedures (Yes/No), and treatment procedures (Yes/No). The study sample included 8,199 adults ≥ 18 years of age who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 26 publications
(30 reference statements)
3
18
0
Order By: Relevance
“…5 Residing in rural areas is associated with poor oral health. [7][8][9][10][11][12][13] Indeed, the rural population is becoming older and sicker. 12 Previous studies evaluating rural and urban oral health reported differences in oral health service utilization 7,10,11 and the oral healthrelated quality of life (OHRQoL).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Residing in rural areas is associated with poor oral health. [7][8][9][10][11][12][13] Indeed, the rural population is becoming older and sicker. 12 Previous studies evaluating rural and urban oral health reported differences in oral health service utilization 7,10,11 and the oral healthrelated quality of life (OHRQoL).…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] Indeed, the rural population is becoming older and sicker. 12 Previous studies evaluating rural and urban oral health reported differences in oral health service utilization 7,10,11 and the oral healthrelated quality of life (OHRQoL). 12,13 Some authors have attributed urban-rural differences in oral health to barriers in access and utilization of dental services, 10,14 with lower access in rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…However, African Americans or Hispanics with diabetes, or diabetic individuals with fewer natural teeth are less likely to have had a dental visit within the past year [ 17 , 18 ]. Additionally, prior studies of the general US adult population have reported that rural residents have lower odds of having received preventive dental procedures or having had a dental visit in the past year compared to metropolitan residents [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sex showed a significant relationship with the utilization of dental services; females had a higher tendency to use dental services than males [50][51][52][53]. Rural areas with a lack of service utility and personnel also have access limitations [54][55][56][57][58][59][60]. However, interventions for children with registered dentist programs did not show significant inequalities based on these factors [61].…”
Section: Discussionmentioning
confidence: 96%